Perceived Core Behavioral Competencies of School Heads: A Framework for Technical Assistance from Teachers' Perspectives - Pilotin, Leonardo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the perceived core behavioral competencies of school heads in Bayombong 2 District and used the findings to develop a framework for technical assistance. Anchored in the Input-Process-Output model, it employed a descriptive survey design involving 20 teachers from 13 public elementary schools selected through purposive sampling. Data were collected using a validated questionnaire with a five-point Likert scale and analyzed through frequency, percentage, and weighted mean. Respondents were predominantly female, married, experienced, pursuing advanced studies, and rated outstanding; all had attended district-level training, although fewer accessed higher-level programs. School heads demonstrated very evident competencies in professionalism and ethics (4.41) and self-management (4.40), while results focus (3.61), teamwork (3.67), service orientation (3.60), and innovation (3.71) were evident. The proposed professional development activities were rated very effective overall (4.55), with collaborative sessions on integrity, ethical standards, and sound decision-making receiving the highest rating (4.85). The study concluded that school heads generally display strong organizational, ethical, collaborative, service-oriented, and innovative leadership behaviors, but continued development remains necessary. It recommended programs on time management, goal setting, ethical leadership, reflective practice, teamwork, communication, negotiation, quality assurance, community engagement, and mentoring. The study supports SDG 4 by strengthening educational leadership for quality learning environments and SDG 16 by promoting ethical, accountable, and effective school governance. Its sustainability impact lies in building enduring institutional capacity, improving leadership systems, supporting responsive service delivery, and sustaining continuous school improvement through structured professional development and technical assistance consistently across the district’s public elementary education system over time.
Keywords: Behavioral Competencies; Educational Leadership; Innovation, Professional Development; Professionalism and Ethics; School Heads; Self-Management; Service Orientation; Technical Assistance; Teamwork